2017
DOI: 10.1016/j.tips.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Designing Safer Analgesics via μ-Opioid Receptor Pathways

Abstract: Pain is both a major clinical and economic problem, affecting more people than diabetes, heart disease, and cancer combined. While a variety of prescribed or over-the-counter (OTC) medications are available for pain management, opioid medications, especially those acting on the μ-opioid receptor (μOR) and related pathways, have proven to be the most effective, despite some serious side effects including respiration depression, pruritus, dependence, and constipation. It is therefore imperative that both academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 73 publications
(119 reference statements)
0
43
0
1
Order By: Relevance
“…PZM21 is therefore very similar to the prototypic opioid morphine, although in vivo it is less potent. While the current dogma is that, for μ receptor agonists, respiratory depression results from activation of arrestin signalling (see Chan et al ., ; Madariaga‐Mazón et al, ; Roth et al, ; Smith et al, ), there is evidence that signalling through G i /G o is also involved in mediating this behaviour. μ Receptor coupling through G i /G o proteins results in activation of G protein‐activated inwardly rectifying potassium channels (GIRKs) and inhibition of voltage‐gated calcium channels (North and Williams, ; Seward et al, ), and it has been reported that the respiratory depression induced by either DAMGO, applied locally in the ventrolateral medulla, or fentanyl, administered systemically, is attenuated in GIRK2 subunit knockout mice (Montandon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…PZM21 is therefore very similar to the prototypic opioid morphine, although in vivo it is less potent. While the current dogma is that, for μ receptor agonists, respiratory depression results from activation of arrestin signalling (see Chan et al ., ; Madariaga‐Mazón et al, ; Roth et al, ; Smith et al, ), there is evidence that signalling through G i /G o is also involved in mediating this behaviour. μ Receptor coupling through G i /G o proteins results in activation of G protein‐activated inwardly rectifying potassium channels (GIRKs) and inhibition of voltage‐gated calcium channels (North and Williams, ; Seward et al, ), and it has been reported that the respiratory depression induced by either DAMGO, applied locally in the ventrolateral medulla, or fentanyl, administered systemically, is attenuated in GIRK2 subunit knockout mice (Montandon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , POMO is a mixed MOR/DOR full agonist, as well as a potent KOR partial agonist. The design of ligands that can act at multiple opioid receptors has emerged as a promising new approach to analgesic drug development to potentially lower side effects and to increase analgesic efficacy, especially in chronic pain conditions ( Ananthan, 2006 ; Kleczkowska et al, 2013 ; Chan et al, 2017 ; Günther et al, 2017 ). All opioid receptors, MOR, DOR, and KOR, are crucial modulators of both nociception and opioid analgesia ( Pasternak, 2014 ; Stein, 2016 ), and are co-localized in nociceptive sensory neurons ( Erbs et al, 2015 ; Massotte, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It facilitates the mutagenesis work, and simplifies the characterization of ligand-binding sites and structural behavior of GPCRs, considering the residue numbering schemes along transmembrane helix residues. The Ballesteros-Weinstein scheme [2] has been more widely accepted for the class A GPCRs over the Oliveira [3], Baldwin [4,5], or Schwartz [6] schemes. This scheme uses two numbers to characterize the residues in each of the seven TM helices: the first number assigns the particular TM helix and the second one corresponds to the residue position related to the most-conserved residue in the particular TM helix which is designated as number 50.…”
Section: The Generic Residue Numbers Of Gpcrsmentioning
confidence: 99%